Business Licensing Policies and Their Economic Impact on the Fashion Industry - Hajar Dewantara; Basri Bado; Soussou Raharimalala (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
The fashion industry has grown rapidly in recent years, driven by economic growth and increasing people's purchasing power. This encourages many people to start businesses in the fashion sector. However, to start a business in the fashion sector, a business permit is required in accordance with applicable regulations. This research aims to analyze business licensing policies and the economic impact on the fashion industry. This research uses qualitative research methods with data collection techniques through literature study, in-depth interviews and participant observation. The research results show that business licensing policies in Indonesia are still complicated and convoluted. This is one of the inhibiting factors for fashion entrepreneurs to start their business. Apart from that, this research also found that business licensing policies have a significant economic    impact on the fashion industry.